First record of the twobar sea bream Acanthopagrus bifasciatus (Teleostei: Sparidae) in the Mediterranean Sea - BEN-SOUISSI, J.; BOUGHEDIR, W.; RIFI, M.; CAPAPE, C.; AZZURRO, E. (Mediterranean Marine Science, 2014)
In September 2010, one specimen of the twobar seabream Acanthopagrus bifasciatus was recorded for the first time in the Mediterranean Sea, off the Islands of Zembra (Gulf of Tunisi: 37°07’03’’N; 10°48’35’’E). This species could have entered the Mediterranean via the Suez Canal or alternatively by unintentional human transport.